Storability of paprika varieties measured by non-destructive acoustic method - Muha, V.; Istella, S.; Tompos, D. (International Journal of Horticultural Science, 2005)
During our experiments, the storability of paprika (Capsicum annuum) samples was measured by a non-destructive acoustic method. The aims of our work were the determination of the applicability and reproducibility of the acoustic stiffness method for paprika, the investigation of the optimum measuring conditions. In order to compare the main paprika varieties regarding shelf-life, our further aim was to follow the softening phenomenon or textural changes (i.e. changes in stiffness) of different paprika varieties measured by the nondestructive acoustic stiffness method. Five different varieties of paprika grown in hydroponics growing system were used for the measurements. All paprika varieties were stored at 20 °C for two weeks. Samples were tested on every 2nd or 3rd day. The acoustic method was found to be suitable to follow the softening of paprika samples. The characteristic frequency of the acoustic signal could be well detected and clearly separated from the other vibration peaks. Tapping the top of the paprika was observed to give a clearer and less noisy signal compared to the signal obtained by tapping the sample’s shoulder. The acoustic results showed the same tendencies with regard to softening during storage as the impact method showed in our previous experiments.